Estimation of genetic parameters for behavioral assessment scores in Labrador retrievers, German shepherd dogs, and golden retrievers - Schiefelbein, Kelly Mae (Kansas State University, 2012)
Among working dogs, the role of a guide dog ranks as one of the most noble and useful occupations and thus was recognized early as a category of working dogs worthy of focused research. Behavior issues top the list of most common reasons for rejecting dogs from working as guides. The objective of this study was to estimate genetic parameters for each of the 101 questions and 12 subscale factors measured by the Canine Behavioral Assessment and Research Questionnaire (C-BARQ). The C-BARQ is a standardized questionnaire that contains seven behavioral categories: training and obedience, aggression, fear and anxiety, separation-related behavior, excitability, attachment and attention-seeking, and a miscellaneous category. These categories and questions allow the evaluator to describe any dog's behavior. For this study, questionnaire responses were obtained on 3,149 and 3,348 Labrador Retrievers (LR) from Guiding Eyes for the Blind (GEB) and 989 and 1,187 Labrador Retrievers, 608 and 692 Golden Retrievers (GR), and 966 and 1,348 German Shepherd Dogs (GSD) from The Seeing Eye, Inc. (TSE) at 6- and 12-months of age, respectively. The estimates of heritability and standard errors from TSE dogs indicate that there is much genetic variation that could be exploited in selection against "Familiar dog-directed aggression/fear" (0.27 ± 0.12) of GR at 6-months, "Chasing" (0.22 ± 0.10) of GR at 6-months, and "Nonsocial fear" (0.27 ± 0.09) of GR at 12-months or in selection for improved "Trainability" of LR (0.46 ± 0.07), GSD (0.47 ± 0.07), and GR (0.20 ± 0.08) at 12-months. In general, the remaining factors and most of the 101 questions were found to be lowly heritable (< 0.10). These estimates are useful to understand more about the nature of behavioral traits leading to the production of successful working guides.
Keywords: Canine; Genetic; Heritability; Guide Dog; C-BARQ; Behavior; Animal Sciences (0475)